The Agrobacterium tumefaciens virD3 gene is not essential for tumorigenicity on plants. - Vogel, A M (1992)
Genetic studies indicate that three of the four polypeptides encoded within the virD operon of the Agrobacterium tumefaciens Ti plasmid are essential for virulence. In order to determine whether the fourth polypeptide, VirD3, has any role in virulence, complementation analysis was used. An A. tumefaciens strain, A348 delta D, which lacked the entire virD operon in the Ti plasmid pTiA6, was constructed. Plasmids containing defined regions of the virD operon were introduced into this strain, and virulence was tested by the strains' abilities to form tumors on Kalanchoe leaves, tomato stems, and potato tubers. As expected, deletion of the virD operon led to an avirulent phenotype. The virulence of this strain could be restored by providing virD1, virD2, and virD4 in trans. No requirement for virD3 in tumor formation was observed in these assays.